Układ osadniczo-gospodarczy województwa dolnośląskiego - Korenik, Stanisław (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The main aim of this article is showing basic tendencies of development of Lower Silesia province's colonial and economic system which has just now occured in situation of definition and forming of development's directions, coming inter alia off process of integration with European Union. Basic problem of this region's spatial structure, threatening social and economic cohesion are disparities not only in area's formation, climate, population's dislocation but also economic activity. Peculiar features of this space decide on the first hand about its potential and economic power and on the other hand they can make barriers in development, as for example: wealthy supply of copper's ores or layers of brown coal.In the article it was also paid special attention for intensive development's phenomenon of Wroclaw metropolitan area following in direction of multifunctional metropolis.As a reason of the elaboration's limited volume presented matters, opinions and conclusions were depicted in synthetic form. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 44-49